THEORETICAL DESIGN OF THE ACTIVITIES OF SUBJECTS OF PRE-CONSCRIPTION MILITARY EDUCATION IN THE DIDACTIC PROCESS (Web of Teachers: Inderscience Research, 2025)
In the article, the design culture of the officer-teacher and students in the didactic processes has a special place. In this case, education and training methods, design become a means of realizing the qualities embodied in the personality of the pedagogue and transferring moral qualities from him to the student. Therefore, it is necessary to consider pedagogical skill as a set of qualities of a teacher's personality and to recognize that it is related to the teacher's high level of psychological and pedagogical training. The interview is conducted in different ways depending on the situation. One of them is individual, that is, one-on-one conversation. Individual education of students cannot be imagined without individual conversations. Such conversations undoubtedly have a great impact on any military serviceman. A detailed analysis of the concepts of "competency", "military professional competence", "project activity", military professional competence. The content of the concepts of reflexive competence, social competence, personal competence, individual competence, basic competences is explained. Humanism in a broad sense is a historically changing system of views that defines a person as a value, his right to freedom, happiness, manifestation and development of his abilities, human development in the evaluation criteria of social institutions, humanity - between individuals the expected normative attitude is discussed.